Reflection on Network Element Evolution of Big Data Management for Telecom Operators - Jun Zhao; Yirong Shi (Dianxin kexue)
Big data has had a profound impact on the future of telecommunications operators，and perhaps even subversive type business model change.The present situation of the application of big data and existing problems of telecom operators were analyzed，and the centralized and decentralized big data service models were compared.The big data network element architecture based on scattered data and implementation of the recommendations were proposed.